Role of Imaging in Nondegenerative Arthritis in Low- and Middle-Income Countries - Suwal, Sundar; Singh, Ashish; Dzefi-Tettey, Klenam; Buchanan, Mary Elizabeth (Seminars in Musculoskeletal Radiology, 2025)
Arthritis is an important cause of disability globally, with high prevalence in low- and middle-income countries. Although osteoarthritis is the most common type of arthritis, various types of nondegenerative arthritis are prevalent in low- and middle-income countries. Multiple imaging modalities, such as radiography, ultrasound, computed tomography, and magnetic resonance imaging, are helpful in diagnosing and prognosticating arthritis. Although imaging appearances can overlap between types of arthritis, specific imaging findings have been described for the different etiologies. Knowing these imaging findings, especially on radiographs and ultrasound in resource-constrained areas, can be helpful in managing arthritis effectively.
Keywords: depositional arthritis; imaging; inflammatory arthritis; lower socioeconomic status